Frontispiece: Perovskite Solar Cells: From the Laboratory to the Assembly Line. Issue 13 (2nd March 2018) - Abate, Antonio; Correa‐Baena, Juan‐Pablo; Saliba, Michael; Su'ait, Mohd Sukor; Bella, Federico
Abstract : The transition from the laboratory scale to the industrial product presents the milestone for perovskite solar cell technology. With this undisputed role in photovoltaics, the development of low‐cost and easy‐to‐scaled‐up materials and processes is a key goal to be achieved within the next five years. In their Review article onpage 3083 ff. F. Bella et al. outline the critical issues and possible solutions in this field, showing how each device component influences efficiency and long‐term stability. Chemistry will play a fundamental role in finding a compromise between all of the relevant aspects of this technology.